Influencing Buying Decisions Through Guerilla And Experiential Marketing: Mediating And Moderating Effects - Siahaan, Febri Sari; Rismanto, Caesar; Purnawan, Lesna; Restika, Dea; Syamsul, Albab (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose - This study aims to analyze the impact of Guerilla Marketing and Experiential Marketing on consumer buying decisions, with Brand Awareness and Brand Trust as moderating variables. Novelty - This study integrates both Guerilla Marketing and Experiential Marketing strategies and explores the mediating and moderating roles within the context of consumer buying decisions. This approach differs from previous studies by providing a more comprehensive understanding of how these two marketing strategies influence buying decisions in the Indonesian creative industry sector. Method - This study uses a quantitative approach with a survey method to examine the effects of guerrilla marketing and experiential marketing on buying decisions, with purchase intention as a mediating variable and brand awareness and brand trust as moderating variables. A sample of 200 consumers of CV. Giribelah Indah was selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) to test direct, mediating, and moderating relationships among variables. Findings - The results show that both Guerilla Marketing and Experiential Marketing have a positive and significant effect on buying decisions. Brand Awareness and Brand Trust strengthen the relationship between marketing strategies and consumer behavior. Purchase intention also plays a significant role in the decision-making process. Limitations and Implications - This study is limited to the creative industry sector, specifically CV. Giribelah Indah, so the findings may not be generalized to other sectors. The implications of this study provide practical insights for marketers to optimize Guerilla Marketing and Experiential Marketing strategies.